Onset of Oscillatory Convection of a Chemically Reacting Fluid with Rigid Horizontal Boundaries - Reddy, G. Shiva Kumar; Ravi, Ragoju (Discontinuity, Nonlinearity, and Complexity, 2026)
A linear stability analysis determining the onset of convection of a chemically reacting fluid in a horizontal layer with rigid boundaries is performed. The governing dimensionless equations are solved using the normal modes, which leads to an eigenvalue problem for the onset of convection. The effects of the solute Rayleigh number, Prandtl number, Lewis number, and Damkohler number on the stability of the system are investigated. We find that the Damkohler number has a contrasting effect on stationary and oscillatory instability. The frequency decreases with χ , but increases with Le and Pr. The effect of increasing the Prandtl number is to advance the onset of convection. The Lewis number has a destabilizing effect on the onset of oscillatory convection.